A brief survey of Buddhist ascetic practices - Muhammad Kamal Hassan, (Universiti Kebangsaan Malaysia, 1977)
The aim of this paper is to isolate the salient features of Buddhist ascetic practices which are regarded by orthodoxy as a essential mode of existence modeled on the life-style of Gotama Buddha. The behaviour of those who subscribe to the regimen is supposed to be "... throughly purified, the course well fulfilled, body and speech well guarded, the conduct of the mind throughly purified, energy well exerted, fear allayed, false view of self gone to destruction... there is abhorrence of evil, delight in aloofness and constant diligence.